2
$\begingroup$

Can someone please explain the steps/rules I need to preform to find the derivative of

$h(t)= \sin (\cos^{-1}t)$?

I tried to used the product rule, and realized it was obviously a failure. Using the chain rule I get:

$\frac{dy}{dx}= \cos(\cos^{-1}t)\frac{-t}{\sqrt{1-t^2}}$

I know I am not finished, what am I supposed to do with this?

$\endgroup$
  • $\begingroup$ First, that should be dh/dt, not dy/dx. Secondly, why are you not finished? That's the derivative. $\endgroup$ – foobar1209 Mar 17 '14 at 4:37
  • $\begingroup$ Well, the only thing you can apply here is the chain rule, of course: you have composition of two functions, not a product. You're indeed almost finished, just change that $\;-t\;$ to $\;-1\;$ and you're done. $\endgroup$ – DonAntonio Mar 17 '14 at 4:39
  • $\begingroup$ Oops, I missed the mistake that @DonAntonio pointed out. It does need to be changed. $\endgroup$ – foobar1209 Mar 17 '14 at 4:41
  • $\begingroup$ Okay, I see my mistake with the t needing to be 1, but I don't understand the rest of it because before coming here, I checked solutions to my book which showed: h(t)= sin (arccos t)= sqrt(1-t^2) therefore, h'(t)= [(1/2)(1-t^2)^(-1/2)][-2t]= -t/sqrt(1-t^2) $\endgroup$ – Mac Mar 17 '14 at 4:46
  • $\begingroup$ Yes, the $\;-t\;$ now appears after $\;\cos\arccos t=t\;$ , not before... $\endgroup$ – DonAntonio Mar 17 '14 at 4:56
2
$\begingroup$

\begin{align} h'(t) &= \frac{d}{dt}\sin(\arccos t) \\ &=\cos(\arccos t) \frac{d}{dt}(\arccos t) & \text{chain rule}\\ &=\cos(\arccos t) \cdot -\frac{1}{\sqrt{1-t^2}} & \text{$\frac{d}{dt}(\arccos t)=-\frac{1}{\sqrt{1-t^2}}$}\\ &=t \cdot -\frac{1}{\sqrt{1-t^2}} & \text{$\cos(\arccos t)=t$}\\ &= \frac{-t}{\sqrt{1-t^2}} \end{align}

$\endgroup$
3
$\begingroup$

You can also make the observation that $h(t)=sin(cos^{-1}(t)) = \sqrt{1-t^2}$ and differentiate from there (do some trig to see where this observation comes from).

\begin{align} (\sqrt{1-t^2})' = \frac{1}{2\sqrt{1-t^2}}\times(1-t^2)'=\frac{-2t}{2\sqrt{1-t^2}}=\frac{-t}{\sqrt{1-t^2}} \end{align}

$\endgroup$
2
$\begingroup$

Use the chain rule:

$$\begin{align}h'(t) &= \cos(\cos^{-1}t)\cdot\frac{d}{dt}(\cos^{-1}t)\\ &=t\cdot\frac{-1}{\sqrt{1-t^2}}\\ &=\frac{-t}{\sqrt{1-t^2}}\end{align}$$

$\endgroup$
2
$\begingroup$

HINT:

If $\displaystyle\cos^{-1}t=u,\cos u =t$

As the Principal values of inverse cosine ratio lies in $\displaystyle\left[0,\pi\right]$

$\displaystyle\sin(\cos^{-1}t)=\sin u\ge0\implies \sin u=+\sqrt{1-\cos^2u}=\sqrt{1-t^2}$

$\endgroup$
  • $\begingroup$ This is exactly what I wasn't understanding from my book as it doesn't explain what changes are being made. I didn't make this connection, Thanks :) $\endgroup$ – Mac Mar 17 '14 at 5:06
  • $\begingroup$ For what it's worth, compositions of the form $\operatorname{trig}_1 \left( \operatorname{trig}_2^{-1} (t) \right)$, where $\operatorname{trig}_1$ and $\operatorname{trig}_2$ are any of the six trigonometric functions, are always equivalent to rational expressions, whose numerators and denominators are expressions of the form $1$, $t$, $\sqrt{1 + t^2}$, or $\sqrt{1 - t^2}$. I call these Pythagorean expressions, as they form the labels of the sides of a right triangle. $\endgroup$ – Sammy Black Mar 17 '14 at 5:46
  • $\begingroup$ The previous comment is for the OP. $\endgroup$ – Sammy Black Mar 17 '14 at 5:47
1
$\begingroup$

If you don't like the function composition, we can also re-arrange this as $ \ \arcsin (h) \ = \ \arccos (t) \ \ $ and use implicit differentiation (along with the known derivatives of these inverse trigonometric functions) to write

$$ \frac{d}{dt} \ [\arcsin (h)] \ = \ \frac{d}{dt} \ [\arccos (t)] $$

$$ \Rightarrow \ \ \frac{1}{\sqrt{1 \ - \ h^2}} \ \cdot \ \frac{dh}{dt} \ = \ -\frac{1}{\sqrt{1 \ - \ t^2}} \ \ \Rightarrow \ \ \frac{dh}{dt} \ = \ -\frac{\sqrt{1 \ - \ h^2}}{\sqrt{1 \ - \ t^2}} \ \ . $$

But since $ \ h(t) \ = \ \sin (\arccos (t)) \ , $ we can apply the Pythagorean Identity to write (with appropriate domain restrictions)

$$ \frac{dh}{dt} \ = \ -\frac{\cos (\arccos (t))}{\sqrt{1 \ - \ t^2}} \ = \ -\frac{t}{\sqrt{1 \ - \ t^2}} \ \ . $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.